Studies on mosquitoes (Diptera: Culicidae) and anthropic environment: 4 - Survey of resting adults and synanthropic behaviour in South-Eastern, Brazil - Oswaldo Paulo Forattini; Iná Kakitani; Eduardo Massad; Daniel Marucci (Universidade de São Paulo, 1993)
Resting adults Culicidae were collected from January 1992 through January 1993 in several habitats of the Ribeira Valley region. The diversity of species found among them suggested that the vegetation remaining within human settlements favored the survival and the population increase of some mosquitoes. Among there are: Ae. scapularis, Ae. serratus, Cx. (Culex), Cx. nigripalpus and Cx. (Melanoconion) such as Cx. ribeirensis. That preservation role may be attributed to the rearing of livestock and the consequent increase in the number of blood sources. These species may be classified as hemisynanthropes and Cx. oedipus apparently evolving to the eusynanthropic status. On the other hand, An. cruzii showed an asynanthropic behaviour, with a low degree of survival in the modified human environment. Epidemiological implications of the data are mentioned.